News about Aggregate Demand and the Business Cycle - Mark Weder; Anca Sirbu; Jang Ting Guo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
We show that an otherwise standard one-sector real business cycle model with variable capital utilization and mild increasing returns-to-scale is able to generate qualitatively as well as quantitatively realistic aggregate fluctuations driven by news shocks to two formulations of future consumption demand or government spending on goods and services. In sharp contrast to many studies in the existing expectations-driven business cycle literature, this result does not rely on non-separable preferences or investment adjustment costs. When the economy is subject to anticipated total factor productivity or investment-specific technology shocks, the relative strength of the intertemporal substitution effect needs to be enhanced for our model to exhibit positive macroeconomic co-movement and business cycle statistics that are consistent with the data.
Keywords: E32; E30; E20; 330